Q. 14

# Prove the following identities:cos3 2x + 3 cos 2x = 4(cos6 x – sin6 x) Proof:

Take RHS:    { a3 – b3 = (a – b) (a2 + b2 + ab)} { cos 2x = cos2 x – sin2 x}  { a2 + b2 + 2ab = (a + b)2} { cos2 x + sin2 x = 1}  { sin 2x= 2 sin x cos x}  { sin2 x = 1 – cos2 x}     = LHS

Hence Proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Conditional Identities31 mins  Trigonometric Functions - 0568 mins  Trigonometric Functions - 0152 mins  Graphs of trigonometric ratios | Trigonometric Identities39 mins  Quiz on Graph of Trigonometric Ratios40 mins  Trigonometric Functions - 0366 mins  Trigonometric Functions - 0658 mins  Trigonometric Series45 mins  Interactive Quiz on trigonometric ratios & identities73 mins  Trigonometric Functions - 0268 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 